Modified regenerated collagen fiber, method for producing same, and headwear product comprising same

By adding benzoic acid and polyvalent metal ions to regenerated collagen fibers, the problems of water resistance and thermal stability of regenerated collagen fibers are solved, and their mechanical strength and thermal shape memory ability are improved, making them suitable for headwear products.

CN119256129APending Publication Date: 2025-01-03KAO CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041055.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-18
Filing Date
2023-05-15
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing regenerated collagen fibers have high water absorption, low mechanical strength, poor thermal stability, and lack thermal shape memory, which affects their application in fiber products.

Method used

By immersing regenerated collagen fibers in a fiber treatment agent containing benzoic acid or its salts, polyvalent metal ions are combined to improve the fiber's water resistance, thermal stability, and stretchability, and to impart thermal shape memory capabilities.

Benefits of technology

It improves the water resistance and thermal stability of regenerated collagen fibers, enhances their mechanical strength and stretchability in wet and dry conditions, and endows them with thermal shape memory capabilities, resulting in excellent surface feel and colorfastness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138542460000161
    Figure BDA0005138542460000161
  • Figure BDA0005138542460000241
    Figure BDA0005138542460000241
Patent Text Reader

Abstract

The present invention relates to a modified regenerated collagen fiber which is improved in water resistance and heat resistance, which are problems of regenerated collagen fibers, imparts thermal shape memory ability, has excellent stretchability (toughness) and surface texture, and is free from discoloration. The modified regenerated collagen fiber according to the present invention contains 1.0 mass% or less of a component (A) in terms of benzoic acid in the regenerated collagen fiber. (A) Benzoic acid or a salt thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a regenerated collagen fiber endowed with water resistance, heat resistance and thermal shape memory, and preferably relates to a regenerated collagen fiber used in fiber products such as wigs, hair extensions and other headdresses. Background Art

[0002] Regenerated collagen fibers are generally different from synthetic fibers and have a natural feel and appearance derived from natural raw materials. The regenerated collagen fibers can be obtained by solubilizing acid-soluble collagen or insoluble collagen with alkali or enzyme to prepare a spinning solution, and then ejecting it into a coagulation bath through a spinning nozzle for fiberization.

[0003] However, regenerated collagen fibers are generally more hydrophilic than synthetic fibers, so they have a higher water absorption rate and extremely low mechanical strength when they contain a large amount of water. Therefore, when washed, the mechanical strength is significantly reduced due to the high water absorption rate, and they break when dried afterwards, resulting in low adaptability as fiber products such as headwear products.

[0004] In addition, regenerated collagen fibers have a problem of low heat resistance. For example, when heat-setting with a hair iron or the like is performed at a high temperature similar to that of human hair, the fibers shrink or curl, thereby impairing their appearance.

[0005] In addition, in the case of plastic synthetic fibers, the shape formed when heat-set using a hair iron or the like continues to be remembered even after subsequent washing (having thermal shape memory capability), but the shape formed when heat-set using a hair iron or the like for regenerated collagen fibers is lost after a subsequent washing (having no thermal shape memory capability), and therefore, compared with existing plastic synthetic fibers, they are inferior in terms of the degree of freedom in shape setting.

[0006] The above points are the main reasons that hinder the popularization of regenerated collagen fibers in fiber products. In particular, the influence caused by the reduction of water resistance, that is, the mechanical strength when wet, is significant.

[0007] On the other hand, in the field of human hair fibers, there is known a method of allowing specific aldehyde derivatives and phenol compounds to act on human hair fibers that originally do not have thermal shape memory properties in order to newly impart thermal shape memory properties (Patent Document 1).

[0008] (Patent Document 1) Japanese Patent Application Publication No. 2019-143281 Summary of the invention

[0009] The present invention provides a modified regenerated collagen fiber, wherein the regenerated collagen fiber contains 1.0 mass % or more of the following component (A) in terms of benzoic acid,

[0010] (A) Benzoic acid or its salt.

[0011] In addition, the present invention provides a method for treating regenerated collagen fibers, comprising the following steps (i):

[0012] Step (i): a step of immersing regenerated collagen fibers in a fiber treatment agent containing the following component (A),

[0013] (A) Benzoic acid or its salt.

[0014] In addition, the present invention provides a method for producing modified regenerated collagen fibers, which comprises the step of treating the regenerated collagen fibers by the above-mentioned method for treating the regenerated collagen fibers.

[0015] In addition, the present invention provides a method for manufacturing a headwear product, which includes: a step of treating regenerated collagen fibers using the above-mentioned regenerated collagen fiber treatment method.

[0016] Furthermore, the present invention provides a headwear product comprising the above-mentioned modified regenerated collagen fiber as a constituent element. DETAILED DESCRIPTION

[0017] In the production of fiber products, fibers are sometimes strongly stretched, and the stretchability (toughness) of the treated fibers is sometimes insufficient in the technology described in Patent Document 1. Therefore, in order to prevent breakage during stretching, it is required to improve the stretchability of the treated fibers.

[0018] Furthermore, in the technique described in Patent Document 1, fibers may be colored.

[0019] Therefore, the present invention relates to a modified regenerated collagen fiber which can improve water resistance and heat resistance, which are problems of regenerated collagen fibers, and impart thermal shape memory capability, and is excellent in stretchability (toughness) and surface touch, and is not colored.

[0020] The present inventors have conducted intensive research and found that in modified regenerated collagen fibers containing benzoic acid or its salt, the carboxyl group of the benzoic acid or its salt is strongly coordinated to the metal (mainly a polyvalent metal) in the regenerated collagen fibers, so that the inside of the fibers is hydrophobized and the leakage of benzoic acid or its salt from the fibers can be prevented. As a result, the water resistance and heat resistance of the modified regenerated collagen fibers in both dry and wet conditions are improved, and not only can the modified regenerated collagen fibers be given a shape by heat setting, but also surprisingly, the elasticity (toughness) is improved compared to before the treatment to a level close to that of human hair, and there is no coloration associated with the modification treatment, thereby completing the present invention.

[0021] According to the present invention, it is possible to provide a modified regenerated collagen fiber which has improved water resistance and heat resistance, which are problems of regenerated collagen fibers, is endowed with thermal shape memory, has improved stretchability (toughness) and surface feel, and is not colored.

[0022] [Fibers to be treated in the present invention]

[0023] The fibers to be treated in the present invention are artificially produced fibers using polymers or oligomers derived from collagen as raw materials, that is, regenerated collagen fibers using collagen as raw materials.

[0024] Regenerated collagen fibers can be manufactured by known techniques. In addition, the composition does not need to be 100% collagen, and may contain natural or synthetic polymers or additives for improving quality. In addition, the regenerated collagen fibers may also be post-processed. As the form of the regenerated collagen fibers, filaments are preferred. The filaments are usually taken out from a bobbin-wound or boxed state. In addition, the filaments obtained from the drying process in the manufacturing process of the regenerated collagen fibers may also be directly used.

[0025] The raw material of collagen used in the manufacture of regenerated collagen fibers is preferably split leather. Split leather can be obtained, for example, from fresh split leather or salted raw leather obtained by slaughtering livestock such as cattle. Most of these split leathers are composed of insoluble collagen fibers, but they are usually used after removing the meaty part attached in a reticular manner and removing the salt used to prevent corruption and deterioration.

[0026] The insoluble collagen fibers contain impurities such as lipids such as glycerides, phospholipids, and free fatty acids, and proteins other than collagen such as glycoproteins and albumins. These impurities, when fibrosis is carried out, will have a great influence on the spinning stability, quality such as gloss or stretching, and odor. Therefore, it is preferred to perform, for example, lime soaking to hydrolyze the fat components in the insoluble collagen fibers, and after the collagen fibers are untied, perform acid / alkali treatment, enzyme treatment, solvent treatment, and other leather treatments that are usually performed in the past to remove these impurities in advance.

[0027] The insoluble collagen treated as above is subjected to solubilization treatment in order to cut the cross-linked peptide part. As the method for the solubilization treatment, the commonly used known alkali solubilization method, enzyme solubilization method, etc. can be applied. In addition, the above-mentioned alkali solubilization method and enzyme solubilization method can also be used in combination.

[0028] When the alkali solubilization method is applied, neutralization is preferably performed with an acid such as hydrochloric acid. In addition, as an improved method of the conventionally known alkali solubilization method, the method described in Japanese Patent Publication No. 46-15033 can also be used.

[0029] The enzymatic solubilization method has the advantage of being able to obtain solubilized collagen with uniform molecular weight, and is a method that can be preferably used in the present invention. As the enzymatic solubilization method, for example, methods described in Japanese Patent Publication No. 43-25829 and Japanese Patent Publication No. 43-27513 can be used.

[0030] When the collagen thus solubilized is further subjected to pH adjustment, salting out, water washing, solvent treatment, and the like, regenerated collagen fibers having excellent quality can be obtained, and therefore, such treatments are preferably performed.

[0031] The solubilized collagen obtained is dissolved with an acid such as hydrochloric acid, acetic acid, lactic acid, etc., and adjusted to a collagen aqueous solution having a pH of 2 to 4.5 and a collagen concentration of 1% by mass or more, preferably 2% by mass or more, and 15% by mass or less, preferably 10% by mass or less. The above-mentioned collagen aqueous solution may also be filtered as needed in order to implement degassing under reduced pressure stirring or to remove fine garbage that is a water-insoluble component. In addition, the above-mentioned collagen aqueous solution may also be further mixed with an appropriate amount of additives such as stabilizers, water-soluble polymer compounds, etc. as needed, for the purpose of improving mechanical strength, improving water resistance and heat resistance, improving gloss, improving spinnability, preventing coloration, and preserving corrosion.

[0032] The above collagen aqueous solution is discharged, for example, through a spinning nozzle or a slit, and immersed in an inorganic salt aqueous solution to form regenerated collagen fibers. As an inorganic salt aqueous solution, an aqueous solution of a water-soluble inorganic salt such as sodium sulfate, sodium chloride, ammonium sulfate, etc. can be used. Usually, the concentration of the inorganic salt in these inorganic salt aqueous solutions is adjusted to 10 to 40% by mass. The pH of the inorganic salt aqueous solution is preferably 2 or more, more preferably 4 or more, and preferably 13 or less, more preferably 12 or less. The pH adjustment can be performed using metal salts such as sodium borate and sodium acetate, hydrochloric acid, boric acid, acetic acid, sodium hydroxide, etc. If the pH of the inorganic salt aqueous solution is within the above range, the peptide bonds of the collagen are not easily hydrolyzed, and the target fibers are easily obtained. In addition, the temperature of the inorganic salt aqueous solution is not particularly limited, but from the viewpoint that the soluble collagen is not denatured, the strength of the fiber obtained by spinning is not reduced, and stable silk is easily produced, it is usually preferably below 35°C. In addition, the lower limit of the temperature of the inorganic salt aqueous solution is not particularly limited, but it can usually be appropriately adjusted according to the solubility of the inorganic salt.

[0033] The regenerated collagen fibers may also be immersed in an epoxy compound or a solution thereof to pre-treat the regenerated collagen fibers (cross-linking treatment). The amount of the epoxy compound is preferably 0.1 equivalents or more, more preferably 0.5 equivalents or more, and further preferably 1 equivalent or more relative to the amount of amino groups in the regenerated collagen fibers that can react with the epoxy compound as determined by amino acid analysis. In addition, it is preferably 500 equivalents or less, more preferably 100 equivalents or less, and further preferably 50 equivalents or less. By keeping the amount of the epoxy compound within the above range, the regenerated collagen fibers can be given a sufficient insolubilization effect in water, and it is also preferred in terms of industrial operability and environment.

[0034] The epoxy compound can be used directly or dissolved in various solvents. As solvents, for example, water; alcohols such as methanol, ethanol, isopropanol; ethers such as tetrahydrofuran and dioxane; halogen organic solvents such as dichloromethane, chloroform, carbon tetrachloride; neutral organic solvents such as dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). These solvents can be used alone or in combination. When water is used as a solvent, an aqueous solution of an inorganic salt such as sodium sulfate, sodium chloride, ammonium sulfate, etc. can be used as needed. Usually, the concentration of the inorganic salt in the aqueous solution of the inorganic salt is adjusted to 10 to 40% by mass. In addition, the pH of the aqueous solution can be adjusted by metal salts such as sodium borate and sodium acetate, or hydrochloric acid, boric acid, acetic acid, sodium hydroxide, etc. In this case, the pH of the aqueous solution is preferably 6 or more, and more preferably 8 or more, from the viewpoint that the reaction of the epoxy group of the epoxy compound with the amino group of the collagen will not be slowed down and the water insolubility is sufficient. Furthermore, since the pH of an aqueous solution of an inorganic salt tends to decrease gradually over time, a buffer may be used as necessary.

[0035] The treatment temperature of the regenerated collagen fibers with the epoxy compound is preferably 50° C. or lower from the viewpoint that the regenerated collagen fibers are not denatured, the strength of the obtained fibers is not reduced, and stable yarns can be easily produced.

[0036] The regenerated collagen fibers may then be washed, oiled, and dried. Washing may be performed, for example, by washing with running water for 10 minutes to 4 hours. As the oil used in the oiling, an emulsion of amino-modified silicone, epoxy-modified silicone, polyether-modified silicone, etc. and an oil composed of a Pluronic type polyether antistatic agent may be used. The drying temperature is preferably below 100°C, more preferably below 75°C.

[0037] As the regenerated collagen fiber to be treated, from the viewpoint of improving water resistance, it is preferred to contain a polyvalent metal or its salt or its complex. As polyvalent metals, calcium, magnesium, strontium, barium, zinc, chromium, aluminum, titanium, zirconium, tin, lead, antimony, iron, copper, etc. can be listed. From the viewpoint of improving water resistance, reducing the coloring of the fiber, reducing the impact on the environment, and improving economic efficiency, aluminum, zirconium, and titanium are preferably used, and aluminum is more preferably used. The content of the polyvalent metal or its salt or its complex in the regenerated collagen fiber is preferably 1.0% by mass or more, more preferably 2.0% by mass or more, more preferably 3.0% by mass or more, and further preferably 5.0% by mass or more, from the viewpoint of improving the touch of the fiber surface, preferably 40% by mass or less, more preferably 30% by mass or less, more preferably 20% by mass or less, and further more preferably 10% by mass or less.

[0038] That is, from the above-mentioned viewpoint, the content of the polyvalent metal or its salt or its complex in the regenerated collagen fibers to be treated is preferably 1.0 to 40 mass %, more preferably 2.0 to 30 mass %, further preferably 3.0 to 20 mass %, and further more preferably 5.0 to 10 mass %, calculated as the amount of the metal element.

[0039] 〔Fiber processing method〕

[0040] (Basic processing)

[0041] The fiber processing method of the present invention includes the following step (i), thereby being able to produce modified regenerated collagen fibers that have improved water resistance and heat resistance, which are problems with regenerated collagen fibers, are endowed with thermal shape memory, have improved stretchability (toughness) and surface feel, and are not colored.

[0042] Step (i): a step of immersing regenerated collagen fibers in a fiber treatment agent containing the following component (A),

[0043] (A) Benzoic acid or its salt.

[0044] The content of the component (A) in the fiber-treating agent used in the step (i) varies depending on the pH range of the fiber-treating agent, but is preferably in the range shown below.

[0045] When the pH of the fiber treatment agent is 2.0 or more and less than 6.5, the content of the component (A) in the fiber treatment agent is preferably 0.8% by mass or more, more preferably 3.0% by mass or more, further preferably 5.0% by mass or more, further preferably 10% by mass or more, further preferably 15% by mass or more, further more preferably 20% by mass or more, in terms of benzoic acid, from the viewpoint of imparting high shape retention, water resistance, stretchability (toughness, i.e., high elongation at break when the fiber is stretched), and heat resistance to the modified regenerated collagen fibers after the treatment. Furthermore, from the viewpoint of improving the touch of the fiber surface, it is preferably 90% by mass or less, more preferably 80% by mass or less, further preferably 70% by mass or less, further more preferably 50% by mass or less, further more preferably 40% by mass or less, further more preferably 35% by mass or less.

[0046] That is, when the pH of the fiber treatment agent is 2.0 or more and less than 6.5, the content of component (A) in the fiber treatment agent is preferably 0.8 to 90 mass %, more preferably 3.0 to 80 mass %, further preferably 5.0 to 70 mass %, further more preferably 10 to 50 mass %, further more preferably 15 to 40 mass %, further more preferably 20 to 35 mass % in terms of benzoic acid from the above viewpoint.

[0047] When the pH of the fiber-treating agent is 6.5 or more and 11.0 or less, the content of the component (A) in the fiber-treating agent is preferably 0.8% by mass or more, more preferably 3.0% by mass or more, further preferably 5.0% by mass or more, further preferably 10% by mass or more, further preferably 15% by mass or more, further more preferably 20% by mass or more, further more preferably 25% by mass or more, further more preferably 26% by mass or more, further more preferably 28% by mass or more, further more preferably 30% by mass or more, from the viewpoint of imparting high shape retention, water resistance, stretchability (toughness, i.e., high elongation at break when the fiber is stretched) and heat resistance to the modified regenerated collagen fibers after the treatment, and is preferably 90% by mass or less, more preferably 80% by mass or less, further preferably 70% by mass or less, further more preferably 50% by mass or less, further more preferably 45% by mass or less, further more preferably 40% by mass or less, from the viewpoint of improving the touch of the fiber surface.

[0048] That is, when the pH of the fiber-treating agent is 6.5 or more and 11.0 or less, the content of the component (A) in the fiber-treating agent is, from the above-mentioned viewpoint, preferably 0.8 to 90% by mass, more preferably 3.0 to 80% by mass, further preferably 5.0 to 70% by mass, further preferably 10 to 70% by mass, further more preferably 15 to 50% by mass, further more preferably 20 to 50% by mass, further more preferably 25 to 45% by mass, further more preferably 26 to 45% by mass, further more preferably 28 to 40% by mass, further more preferably 30 to 40% by mass, in terms of benzoic acid.

[0049] The fiber treatment agent used in step (i) uses water as a medium. The water content in the fiber treatment agent is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, further more preferably 40% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 85% by mass or less.

[0050] That is, the water content in the fiber treatment agent is preferably 10 to 95% by mass, more preferably 20 to 90% by mass, further preferably 30 to 85% by mass, and still further preferably 40 to 85% by mass.

[0051] The pH of the fiber treatment agent used in step (i) is preferably 2.0 or more, more preferably 3.0 or more, further preferably 3.5 or more, further more preferably 4.0 or more, and is preferably 11.0 or less, more preferably 10.0 or less, further preferably 9.0 or less, from the viewpoint of damage suppression and durability improvement of the regenerated collagen fibers. In addition, the pH in the present invention is a value at 25°C.

[0052] That is, the pH of the fiber treatment agent is preferably 2.0 to 11.0, more preferably 3.0 to 10.0, further preferably 3.5 to 9.0, and further preferably 4.0 to 9.0, from the viewpoint of suppressing damage to the regenerated collagen fibers and improving durability.

[0053] In step (i), the regenerated collagen fibers subjected to the fiber treatment may be dried or wetted. For example, the regenerated collagen fibers may be directly treated in a state before being dried during production. The amount of the fiber treatment agent impregnated with the regenerated collagen fibers is preferably 2.0 or more, more preferably 3.0 or more, further preferably 5.0 or more, further more preferably 10 or more, further more preferably 20 or more, and preferably 500 or less, more preferably 250 or less, further preferably 100 or less, in terms of the bath ratio relative to the mass of the regenerated collagen fibers (mass of the fiber treatment agent / mass of the regenerated collagen fibers).

[0054] That is, the bath ratio is preferably 2.0 to 500, more preferably 3.0 to 250, further preferably 5.0 to 100, further more preferably 10 to 100, further more preferably 20 to 100.

[0055] In step (i), the regenerated collagen fibers may be fixed in advance with a curling iron or the like, and then subjected to the fiber treatment of the present invention under heating. By doing so, the regenerated collagen fibers can be given thermal shape memory and high durability, while being given a desired shape.

[0056] The immersion of the regenerated collagen fibers in the fiber treatment agent in step (i) is preferably carried out under heating, and the heating is carried out by heating the fiber treatment agent. In addition, the heating can be carried out by immersing the regenerated collagen fibers in the fiber treatment agent in a heated state, but it can also be carried out by immersing the regenerated collagen fibers in the fiber treatment agent at a low temperature and then heating. The temperature of the fiber treatment agent is preferably 20°C or more, more preferably 35°C or more, and further preferably 45°C or more, in order to prevent the regenerated collagen fibers from being denatured and deteriorated due to heat, it is preferably less than 100°C, more preferably less than 80°C, further preferably less than 70°C, and further preferably less than 60°C.

[0057] The immersion time in step (i) is appropriately adjusted according to the heating temperature. For example, from the viewpoint of showing the effect of improving the elasticity of the regenerated collagen fibers, it is preferably 15 minutes or more, more preferably 30 minutes or more, and even more preferably 1 hour or more. In addition, in order to inhibit damage to the regenerated collagen fibers, it is preferably 48 hours or less, more preferably 24 hours or less, and even more preferably 12 hours or less.

[0058] Step (i) is preferably performed under an environment that suppresses evaporation of water. Specific means for suppressing evaporation of water include covering the container of the fiber treatment agent impregnated with the regenerated collagen fibers with a membrane, cap, or lid made of a material that does not permeate water vapor.

[0059] After step (i), the regenerated collagen fibers may or may not be rinsed. However, rinsing is preferably performed from the viewpoint of preventing a decrease in the touch of the regenerated collagen fiber surface due to excess component (A).

[0060] It is believed that the component (A) permeates into the regenerated collagen fiber through the treatment of step (i) and strongly coordinates with the metal, such as a polyvalent metal, in the fiber, thereby producing various effects. That is, by the regenerated collagen fiber treatment method including step (i), it is possible to produce modified regenerated collagen fibers containing the component (A) in the fiber, and the obtained modified regenerated collagen fibers can be shaped by heat setting to become fibers with excellent water resistance, heat resistance, tensile elastic modulus, and highly improved stretchability (toughness) of the regenerated collagen fiber.

[0061] 〔Modified regenerated collagen fiber〕

[0062] Hereinafter, the modified regenerated collagen fibers of the present invention obtained by the above-mentioned method will be described.

[0063] (Component (A): benzoic acid or its salt)

[0064] The modified regenerated collagen fiber of the present invention contains benzoic acid or a salt thereof as a component (A). Examples of the component (A) in the form of a salt include alkali metal salts such as sodium salts and potassium salts.

[0065] The content of component (A) in the modified regenerated collagen fiber of the present invention is 1.0 mass% or more, preferably 5.0 mass% or more, more preferably 10 mass% or more, further preferably 12 mass% or more, and further preferably 15 mass% or more, from the viewpoint of producing a modified regenerated collagen fiber having higher shape retention, water resistance and heat resistance, calculated as benzoic acid. In addition, from the viewpoint of improving the touch of the fiber surface, it is preferably 50 mass% or less, more preferably 40 mass% or less, and further preferably 30 mass% or less.

[0066] That is, from the above-mentioned viewpoint, the content of component (A) in the modified regenerated collagen fiber of the present invention is preferably 1.0 to 50 mass %, more preferably 5.0 to 40 mass %, further preferably 10 to 40 mass %, further more preferably 12 to 40 mass %, and further more preferably 15 to 30 mass %, calculated as benzoic acid.

[0067] (Component (B): polyvalent metal or its salt or its complex)

[0068] The modified regenerated collagen fiber of the present invention preferably further contains (B) a polyvalent metal or its salt or its complex from the viewpoint of improving water resistance. Examples of the polyvalent metal include calcium, magnesium, strontium, barium, zinc, chromium, aluminum, titanium, zirconium, tin, lead, antimony, iron, copper, etc. From the viewpoint of improving water resistance, reducing the coloring of the fiber, reducing the impact on the environment, and improving economic efficiency, aluminum, zirconium, and titanium are preferably used, and aluminum is more preferably used. These can be used alone or in combination of two or more.

[0069] The content of component (B) in the modified regenerated collagen fiber of the present invention is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, further preferably 1.0% by mass or more, further more preferably 2.0% by mass or more, further more preferably 5.0% by mass or more, from the viewpoint of improving water resistance, and is preferably 40% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, further more preferably 10% by mass or less, further more preferably 7.0% by mass or less, from the viewpoint of improving the touch of the fiber surface.

[0070] That is, from the above-mentioned viewpoint, the content of component (B) in the modified regenerated collagen fiber of the present invention is preferably 0.1 to 40 mass %, more preferably 0.5 to 30 mass %, further preferably 1.0 to 20 mass %, further more preferably 2.0 to 10 mass %, and further more preferably 5.0 to 7.0 mass %, calculated as the amount of metal elements.

[0071] The content of the component (A) in the modified regenerated collagen fiber of the present invention in terms of benzoic acid (component (A) 苯甲酸量 ) relative to the content of component (B) in terms of metal elements (component (B) 金属元素量 ) mass ratio (component (A) 苯甲酸量 ) / (ingredient (B) 金属元素量 ) from the viewpoint of producing a fiber having higher shape continuity, water resistance and heat resistance, it is preferably 0.025 or more, more preferably 0.2 or more, further preferably 0.5 or more, further more preferably 1.0 or more, further more preferably 2.0 or more, further more preferably 2.5 or more, and from the viewpoint of producing a fiber having high durability and improving the tactile feel of the fiber surface, it is preferably 100 or less, more preferably 50 or less, further preferably 20 or less, further more preferably 10 or less, further more preferably 8 or less, further more preferably 6 or less, further more preferably 4 or less.

[0072] That is, the mass ratio (component (A)) in the modified regenerated collagen fiber of the present invention is 苯甲酸量 ) / (ingredient (B) 金属元素量 ) From the above viewpoints, it is preferably 0.025 to 100, more preferably 0.2 to 50, further preferably 0.5 to 20, further more preferably 1.0 to 10, further more preferably 2.0 to 8, further more preferably 2.5 to 6, further more preferably 2.5 to 4.

[0073] The modified regenerated collagen fiber of the present invention is a fiber that can be given a shape by heat setting, has excellent water resistance, heat resistance, and tensile elastic modulus, and highly improves the elasticity (toughness) of the regenerated collagen fiber. Therefore, the modified regenerated collagen fiber of the present invention can be used as a fiber for headwear products, and various headwear products can be manufactured using the fiber.

[0074] In addition, as preferred headwear products in the present invention, for example, wigs, hairpieces, highlighted hair, hair extensions, fake braids, hair accessories, and doll hair can be cited.

[0075] The modified regenerated collagen fiber of the present invention can be used alone as a headdress product, or can be mixed with other fibers to form a headdress product. As other fibers, there is no particular limitation as long as they can be used in headdress products. As other fibers, for example, polyester fibers, human hair, animal hair, polyvinyl chloride fibers, modified polyacrylonitrile fibers (modacrylic fibers), polyamide fibers, polyolefin fibers, etc. can be listed. Among them, from the viewpoint of excellent heat resistance, flame retardancy and curl retention, polyester fibers are preferred, and flame retardant polyester fibers are more preferred.

[0076] The flame-retardant polyester fibers are not particularly limited. From the viewpoint of flame retardancy, it is preferred that 5 to 40 parts by mass of brominated epoxy flame retardants be contained relative to 100 parts by mass of one or more polyester resins selected from polyalkylene terephthalates and copolyesters with polyalkylene terephthalates as the main body. In the present invention, "main body" means containing 50 mol% or more, and "copolyester with polyalkylene terephthalates as the main body" means a copolyester containing 50 mol% or more of polyalkylene terephthalates. Preferably, "copolyester with polyalkylene terephthalates as the main body" contains 60 mol% or more, more preferably 70 mol% or more, and further preferably 80 mol% or more of polyalkylene terephthalates. The flame-retardant polyester fibers preferably also contain 0 to 5 parts by mass of antimony compounds relative to 100 parts by mass of polyester resins. By containing antimony compounds, the flame retardancy of polyester fibers is improved.

[0077] With regard to the above-described embodiments, preferred aspects of the present invention will be further disclosed below.

[0078] <1>

[0079] A modified regenerated collagen fiber, wherein the regenerated collagen fiber contains 1.0 mass % or more of the following component (A) as benzoic acid:

[0080] (A) Benzoic acid or its salt.

[0081] <2>

[0082] The modified regenerated collagen fiber as described in <1>, wherein the content of component (A), calculated as benzoic acid, is preferably 5.0 mass % or more, more preferably 10 mass % or more, further preferably 12 mass % or more, further more preferably 15 mass % or more, and is preferably 50 mass % or less, more preferably 40 mass % or less, further preferably 30 mass % or less.

[0083] <3>

[0084] The modified regenerated collagen fiber as described in <1> or <2> preferably further contains the following component (B):

[0085] (B) A polyvalent metal or a salt thereof or a complex thereof.

[0086] <4>

[0087] The modified regenerated collagen fibers as described in <3>, wherein component (B) is preferably one or more polyvalent metals selected from calcium, magnesium, strontium, barium, zinc, chromium, aluminum, titanium, zirconium, tin, lead, antimony, iron and copper, or their salts or complexes thereof, more preferably one or more polyvalent metals selected from aluminum, zirconium and titanium, or their salts or complexes thereof, and further preferably aluminum or its salts or complexes thereof.

[0088] <5>

[0089] The modified regenerated collagen fibers as described in <3> or <4>, wherein the content of component (B), calculated as the amount of metal elements, is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, further preferably 1.0% by mass or more, further more preferably 2.0% by mass or more, further more preferably 5.0% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, further more preferably 10% by mass or less, further more preferably 7.0% by mass or less.

[0090] <6>

[0091] The modified regenerated collagen fiber according to any one of <1> to <5>, wherein the mass ratio of the content of the component (A) as benzoic acid to the content of the component (B) as the metal element (component (A)) is 苯甲酸量 ) / (ingredient (B) 金属元素量 ) is preferably 0.025 or more, more preferably 0.2 or more, further preferably 0.5 or more, further more preferably 1.0 or more, further more preferably 2.0 or more, further more preferably 2.5 or more, and is preferably 100 or less, more preferably 50 or less, further preferably 20 or less, further more preferably 10 or less, further more preferably 8 or less, further more preferably 6 or less, further more preferably 4 or less.

[0092] <7>

[0093] A method for processing regenerated collagen fibers, comprising the following steps (i),

[0094] Step (i): a step of immersing regenerated collagen fibers in a fiber treatment agent containing the following component (A),

[0095] (A) Benzoic acid or its salt.

[0096] <8>

[0097] The method for processing regenerated collagen fibers as described in <7> comprises, before step (i), a step of solubilizing insoluble collagen fibers made from the split hides of livestock animals, ejecting the obtained solubilized collagen aqueous solution through a spinning nozzle or a slit, and immersing the regenerated collagen fibers in an inorganic salt aqueous solution.

[0098] <9>

[0099] The method for treating regenerated collagen fibers as described in <8> preferably includes a cross-linking treatment step of immersing the regenerated collagen fibers in an epoxy compound or a solution thereof after the regenerated collagen fiber production step.

[0100] <10>

[0101] The method for treating regenerated collagen fibers according to any one of <7> to <9>, wherein the regenerated collagen fibers contain the following component (B):

[0102] (B) A polyvalent metal or a salt thereof or a complex thereof.

[0103] <11>

[0104] A method for treating regenerated collagen fibers as described in <10>, wherein component (B) is preferably a polyvalent metal or its salt or its complex selected from calcium, magnesium, strontium, barium, zinc, chromium, aluminum, titanium, zirconium, tin, lead, antimony, iron and copper, more preferably a polyvalent metal or its salt or its complex selected from aluminum, zirconium and titanium, further preferably aluminum or its salt or its complex.

[0105] <12>

[0106] A method for processing regenerated collagen fibers as described in any one of <7> to <11>, wherein the pH of the fiber processing agent used in step (i) at 25°C is preferably above 2.0, more preferably above 3.0, further preferably above 3.5, further more preferably above 4.0, and is preferably below 11.0, more preferably below 10.0, further preferably below 9.0.

[0107] <13>

[0108] A method for treating regenerated collagen fibers as described in any one of <7> to <12>, wherein the pH of the fiber treating agent used in step (i) is greater than 2.0 and less than 6.5, and the content of component (A) in the fiber treating agent, calculated as benzoic acid, is preferably greater than 0.8 mass%, more preferably greater than 3.0 mass%, further preferably greater than 5.0 mass%, further more preferably greater than 10 mass%, further more preferably greater than 15 mass%, further more preferably greater than 20 mass%, and is preferably less than 90 mass%, more preferably less than 80 mass%, further preferably less than 70 mass%, further more preferably less than 50 mass%, further more preferably less than 40 mass%, further more preferably less than 35 mass%.

[0109] <14>

[0110] A method for treating regenerated collagen fibers as described in any one of <7> to <12>, wherein the pH of the fiber treating agent used in step (i) is 6.5 to 11.0, and the content of component (A) in the fiber treating agent, calculated as benzoic acid, is preferably 0.8% by mass or more, more preferably 3.0% by mass or more, further preferably 5.0% by mass or more, further more preferably 10% by mass or more, further more preferably 15% by mass or more, further more preferably 20% by mass or more, further more preferably 25% by mass or more, further more preferably 26% by mass or more, further more preferably 28% by mass or more, further more preferably 30% by mass or more, and is preferably 90% by mass or less, more preferably 80% by mass or less, further preferably 70% by mass or less, further more preferably 50% by mass or less, further more preferably 45% by mass or less, further more preferably 40% by mass or less.

[0111] <15>

[0112] A method for processing regenerated collagen fibers as described in any one of <7> to <14>, wherein the fiber processing agent used in step (i) uses water as a medium, and the water content in the fiber processing agent is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, further more preferably 40% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 85% by mass or less.

[0113] <16>

[0114] A method for treating regenerated collagen fibers as described in any one of <7> to <15>, wherein the amount of the fiber treating agent with which the regenerated collagen fibers are impregnated in step (i) is preferably 2 or more, more preferably 3 or more, further preferably 5 or more, further more preferably 10 or more, further more preferably 20 or more, and is preferably 500 or less, more preferably 250 or less, further preferably 100 or less, in terms of bath ratio relative to the mass of the regenerated collagen fibers (mass of the fiber treating agent / mass of the regenerated collagen fibers).

[0115] <17>

[0116] A method for treating regenerated collagen fibers as described in any one of <7> to <16>, wherein the temperature of the fiber treating agent with which the regenerated collagen fibers are impregnated in step (i) is preferably above 20°C, more preferably above 35°C, and further preferably above 45°C, and is preferably below 100°C, more preferably below 80°C, further preferably below 70°C, and further preferably below 60°C.

[0117] <18>

[0118] A method for treating regenerated collagen fibers as described in any one of <7> to <17>, wherein the immersion time in step (i) is preferably more than 15 minutes, more preferably more than 30 minutes, further preferably more than 1 hour, and is preferably less than 48 hours, more preferably less than 24 hours, further preferably less than 12 hours.

[0119] <19>

[0120] The method for treating regenerated collagen fibers according to any one of <7> to <18>, wherein the step (i) is preferably performed under an environment that suppresses evaporation of water.

[0121] <20>

[0122] A method for producing modified regenerated collagen fibers, comprising: treating regenerated collagen fibers by the method for treating regenerated collagen fibers described in any one of <7> to <19>.

[0123] <21>

[0124] A method for producing a headdress product, comprising: treating regenerated collagen fibers by the method for treating regenerated collagen fibers described in any one of <7> to <19>.

[0125] <22>

[0126] A headwear product comprising the modified regenerated collagen fiber according to any one of <1> to <6> as a constituent element.

[0127] <23>

[0128] The headdress product as described in <22>, wherein the headdress product is selected from wigs, hairpieces, highlighted hair, hair extensions, fake braids, hair accessories and doll hair.

[0129] Example

[0130] Examples 1 to 11, Comparative Examples 1 to 3

[0131] Regenerated collagen fibers were treated and various evaluations were performed by the following methods using the compositions of the formulations shown in Table 1. The pH of each prepared composition was directly measured at room temperature (25° C.) using a pH meter (F-52 manufactured by HORIBA).

[0132] <Handling method>

[0133] 1. Immerse a 22 cm long hair bundle of 0.50 g of regenerated collagen fiber (※) in a container containing a fiber treatment agent in an amount corresponding to the bath ratio shown in the table, seal the container mouth, and immerse the container in a water bath (manufacturer: Toyo Seisakusho Co., Ltd. / model: TBS221FA) at a temperature shown in the table, and heat for the time shown in the table.

[0134] ※: Kaneka's regenerated collagen fibers were purchased in the form of commercially available hair extensions, and the fibers were cut and divided into small bundles for evaluation. In this evaluation, the hair extensions used had the fiber type marked Ultima 100%, the color number 30 white, and the shape straight hair.

[0135] 2. Remove the container containing the hair bundle from the water bath and return to room temperature.

[0136] 3. The hair bundle was taken out of the container, rinsed with 30°C running tap water for 30 seconds, foamed with the evaluation shampoo for 60 seconds, rinsed with 30°C running tap water for 30 seconds, and the water was gently wiped off with a towel. The hair bundle was then blow-dried while being combed with a warm air hair dryer (manufactured by TESCOM, Nobby White NB3000).

[0137] <Evaluation of Shampoo Formulation>

[0138]

[0139] <Increase in average elongation at break during fiber stretching>

[0140] As an index of water resistance and stretchability (toughness) when the fiber is stretched, the average elongation at break, i.e., the average value of a plurality of (10) fibers when the fiber is stretched by stretching and the fiber breaks at a certain percentage relative to the original fiber length, is used. The evaluation is performed according to the following procedure using a hair bundle immediately after being treated by the above-mentioned <Treatment Method>.

[0141] 1. Cut 10 fibers from the root of the hair bundle. Take a 3 cm fiber piece from the middle of the root and the end of each fiber, and get a total of 10 3 cm hair pieces.

[0142] 2. Place the fiber sheet in the "MTT690 Fiber Automatic Tensile Tester" manufactured by DIA-STRON Limited. After being immersed in water for 30 minutes, the automatic measurement is started to obtain the average elongation at break of the fiber immersed in water. The higher the value, the higher the elasticity, the better the toughness, and the better the durability.

[0143] According to the following formula, based on the average elongation at break (A%) of the fiber when directly cut from a commercial product (untreated; Comparative Example 1), the average elongation at break (B%) of the treated hair bundle increased to what extent (C%) compared with the untreated state, which is recorded in the table as "increase rate of average elongation at break when fiber is stretched [%]".

[0144] C(%)=B(%)-A(%)

[0145] <Increase in average breaking load during fiber stretching>

[0146] As an index of water resistance when the fiber is stretched, the average breaking load when the fiber is stretched is used. The evaluation is performed using a hair bundle just after being treated by the above-mentioned <Treatment Method>. In addition, as a numerical value, the average value when evaluating multiple (10) fibers is used. The evaluation is performed according to the following procedures.

[0147] 1. Cut 10 fibers from the root of the hair bundle. Take a 3 cm fiber piece from the middle of the root and the end of each fiber, and get a total of 10 3 cm hair pieces.

[0148] 2. Place the fiber sheet in the "MTT690 Fiber Automatic Tensile Tester" manufactured by DIA-STRON Limited. After being immersed in water for 30 minutes, the automatic measurement starts to determine the breaking load when the fiber is stretched while immersed in water. The higher the value, the more elastic and resistant it is to external forces, and the better the durability.

[0149] The average breaking load (W) of the fiber when it was stretched in a state of being cut directly from a commercial product (untreated; Comparative Example 1) was calculated according to the following formula:0 The average breaking load (W) of the treated hair bundle was taken as the reference. 1 The degree to which the average breaking load (gf)) of the fiber increased from the untreated state (Y(gf)) is recorded in the table as "the increase in the average breaking load when the fiber is stretched [gf]".

[0150] Y(gf)=W 1 (gf)-W 0 (gf)

[0151] <Shrinkage rate when setting with a high-temperature hair curler>

[0152] As an index of heat resistance, the shrinkage rate when setting with a high-temperature hair iron is used. The evaluation is performed using a hair bundle just after being treated by the above-mentioned <Treatment Method>. In addition, as a numerical value, the average value when evaluating multiple (5) fibers is used. The evaluation is performed according to the following procedures.

[0153] 1. Cut 5 fibers from the root of the hair bundle just after being treated by the above <treatment method> and mark them. Measure the length of these 5 treated fibers and record the average value (as the length L). 1 Next, these five fibers after treatment with the marks were bundled together by sandwiching two hair bundles (1 g in total) of 0.5 g of untreated regenerated collagen fibers prepared separately to make a new hair bundle (hereinafter referred to as a large hair bundle), and the entire large hair bundle was ironed three times at a speed of 5 cm / second using a hair straightener (manufactured by Miki Electric Industry Co., Ltd. / Model: AHI-938) set at 180°C.

[0154] 2. After the perm operation, take out the 5 fibers marked with the mark from the large hair bundle, re-measure the length of each of the 5 fibers marked with the mark, and record the average value (as the length L 2 ).

[0155] 3. The shrinkage rate of high-temperature hair curling is defined as S dry = {1-(L 2 / L 1 )}×100[%]. dry The closer to 0%, the less likely the shrinkage due to dry heat occurs, and the better the heat resistance.

[0156] <Shrinkage ratio when heated with hot water>

[0157] As an index of water resistance and heat resistance, the shrinkage rate when heated with hot water is used. The evaluation is performed using a hair bundle just after being treated by the above-mentioned <Treatment Method>. In addition, as a numerical value, the average value when evaluating multiple fibers (5 fibers) is used. The evaluation is performed according to the following procedures.

[0158] 1. Cut 5 fibers from the root of the hair bundle and record the average length of each fiber (as the length L 1 ), and immersed in a 90°C water bath (manufacturer: Toyo Seisakusho Co., Ltd. / model: TBS221FA) and heated for 1 minute.

[0159] 2. After the heating operation, take out 5 fibers, gently wipe off the moisture with a towel, dry them at room temperature and humidity for 30 minutes, and re-record the average length of each fiber (as the length L 2 ).

[0160] 3. Define the shrinkage rate when heated by hot water as S wet = {1-(L 2 / L 1 )}×100[%]. wet The closer to 0%, the less likely the shrinkage due to moisture and heat occurs, and the better the heat resistance.

[0161] <Thermal shape memory capability>

[0162] The thermal shape memory ability was evaluated using the hair bundle immediately after being treated by the above-mentioned <Treatment Method> If the result of "I: Shape imparting (curl)" was 5% or less, it was considered invalid and the subsequent treatment and evaluation were not performed.

[0163] I: Shape giving (curls)

[0164] 1. A 22 cm long hair bundle containing 0.5 g of regenerated collagen fibers was moistened with 30°C tap water for 30 seconds, and the moistened hair bundle was wound around a plastic rod with a diameter of 14 mm and fixed with a clip.

[0165] 2. The hair bundle wound around the rod is immersed in a 60°C water bath (manufacturer: Toyo Seisakusho Co., Ltd. / model: TBS221FA) and heated for 1 minute.

[0166] 3. Take the hair bundle out of the water bath, immerse it in water at 25°C for 1 minute, take it out of the water, and return it to room temperature.

[0167] 4. Remove the hair from the stick, comb it three times, take it out of the water for 3 minutes, and take a photo from the front and side while it is hanging.

[0168] (Evaluation Criteria)

[0169] Set the length of the unprocessed hair strand to L 0 (22 cm), the length of the hair bundle after the treatment is defined as L, and the curl increase rate = hair bundle length reduction rate (I) (%) obtained by the following formula is defined as the curl strength of the curl.

[0170] I=[(L0 -L) / L 0 ]×100

[0171] II: Reshape (straight hair)

[0172] 1. The hair bundle evaluated in I was combed with a comb and then slid with a hair straightener (manufactured by Miki Electric Industry Co., Ltd., model: AHI-938) set at 180°C for 6 times at a speed of 5 cm / sec.

[0173] 2. Rinse with 30°C running tap water for 30 seconds, foam with the evaluation shampoo for 60 seconds, rinse with 30°C running tap water for 30 seconds, and dry with a towel.

[0174] 3. Hang it up and dry it naturally at 20℃ 65% RH for 12 hours. After combing it with a comb, observe it visually from the front and side while it is hanging.

[0175] (Evaluation Criteria)

[0176] Set the length of the unprocessed hair strand to L 0 (22 cm), the length of the hair bundle after the treatment is defined as L, and the straightening rate (ST) (%) calculated according to the following formula is defined as the degree of straightening achieved. When ST = 100%, the hair bundle is completely straightened.

[0177] ST=[1-(L 0 -L) / L 0 ]×100

[0178] III: Reshape (curls)

[0179] 1. The hair bundle evaluated in II was moistened with 30°C tap water for 30 seconds, and then the moistened hair bundle was wound around a plastic rod having a diameter of 14 mm and fixed with a clip.

[0180] 2. The hair bundle wound around the rod is immersed in a 60°C water bath (manufacturer: Toyo Seisakusho Co., Ltd. / model: TBS221FA) and heated for 1 minute.

[0181] 3. Take the hair bundle out of the water bath, immerse it in water at 25°C for 1 minute, take it out of the water, and return it to room temperature.

[0182] 4. Remove the hair from the stick, comb it through 3 times, take it out of the water 3 minutes later, and take a photo from the front and side while it is hanging.

[0183] (Evaluation Criteria)

[0184] Set the length of the unprocessed hair strand to L 0(22 cm), the length of the hair bundle after the treatment is defined as L, and the curl increase rate = hair bundle length reduction rate (I) (%) obtained by the following formula is defined as the curl strength of the curl.

[0185] I=[(L 0 -L) / L 0 ]×100

[0186] <Excellent surface feel>

[0187] Regarding the evaluation of the surface feel, five professional evaluators evaluated the smoothness of the hair immediately after being treated with the <Treatment Method> by hand according to the following criteria, and the total value of the five evaluators was used as the evaluation result.

[0188] (Evaluation Criteria)

[0189] 5: Compared with the untreated fiber (Comparative Example 1), it has a very smooth feel.

[0190] 4: Compared with the untreated fiber (Comparative Example 1), it has a smooth feel.

[0191] 3: Slightly smoother than untreated fiber (Comparative Example 1)

[0192] 2: Same feel as untreated fiber (Comparative Example 1)

[0193] 1: More rough and rough than the untreated fiber (Comparative Example 1), with poor hand feel

[0194] <Suppression of fiber coloration>

[0195] 1. The color of the hair bundle was measured at the root, middle, and ends of the hair using a colorimeter (CR-400, manufactured by Konica Minolta Inc.), and the average value of the six points was taken as the color value (L, a, b).

[0196] 2. The degree of coloration was evaluated by ΔE*ab using an untreated hair tress of color number 30 white (*) (Comparative Example 1) as a reference. In addition, color measurement was performed on the day of treatment.

[0197] (※) Untreated hair color 30 white

[0198] Regenerated collagen fibers manufactured by KANEKA were purchased as commercially available hair extension products, and fibers were cut from them and divided into small bundles for evaluation. In this evaluation, the hair extension products used had the fiber type marked with Ultima 100%, the color number 30 white, and the shape of straight hair.

[0199] Furthermore, these regenerated collagen fibers manufactured by KANEKA Corporation contained aluminum, and the aluminum content obtained by the above-mentioned analysis method was 6.8% by mass in all cases.

[0200] ΔE*ab is measured when the value of the untreated hair bundle of color No. 30 white is set as (L 0 ,a 0 ,b 0 ), the measured value of the treated hair bundle is set to (L 1 ,a 1 ,b 1 ),use〔(L 1 -L 0 ) 2 +(a 1 -a 0 ) 2 +(b 1 -b 0 ) 2 〕 1 / 2 The coloration suppression effect was determined using the following criteria.

[0201] 5: ΔE*ab≤5.0

[0202] 4: 5.0<ΔE*ab≤10.0

[0203] 3: 10.0<ΔE*ab≤15.0

[0204] 2: 15.0<ΔE*ab≤20.0

[0205] 1:20.0<ΔE*ab

[0206] <Quantitative determination of benzoic acid>

[0207] The amount of benzoic acid contained in the treated regenerated collagen fibers was quantified by the following method and is indicated in the table as "Component (A) 苯甲酸量 " (No measurement was performed on Comparative Examples 2 and 3).

[0208] Reagents

[0209] 6N hydrochloric acid: titration solution for volumetric analysis, manufactured by Kanto Chemical Co., Ltd.

[0210] Sodium acetate: Special grade, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0211] Acetic acid: Special grade, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0212] Acetonitrile: for LC / MS, manufactured by Kanto Chemical Co., Ltd.

[0213] Sodium benzoate: Special grade, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0214] Ultrapure water: Ultrapure water production equipment Milli Q water, made by Millipore

[0215] Quantitative method

[0216] The sample was cut into pieces, accurately weighed to about 10 mg, and 3 mL of 6N hydrochloric acid was added, and heated at 50°C for 15 hours to dissolve it. After cooling, it was filtered and the filtrate was used as the sample solution. In addition, sodium benzoate was dissolved in the mobile phase to prepare a solution with a concentration of 0.1 to 100 μg / mL in terms of benzoic acid, which was used as the standard solution for preparing the standard curve. The sample solution and the standard solution were tested by liquid chromatography to measure the peak area of ​​the sample solution and the peak area of ​​the standard solution.

[0217] ·Measurement conditions

[0218] Detector: UV-Visible Photometer

[0219] Measurement wavelength: 230nm

[0220] Chromatographic column: A stainless steel tube with an inner diameter of 21 mm and a length of 150 mm was filled with 5 μm octadecylsilylated silica gel for liquid chromatography.

[0221] Column temperature: a certain temperature around 40℃

[0222] Mobile phase: After dissolving about 0.68 g of sodium acetate and 0.91 g of acetic acid in 750 mL of ultrapure water, add 250 mL of acetonitrile and mix.

[0223] HPLC / UV conditions

[0224] Apparatus: UltiMate 3000 system (manufactured by Thermo Fisher Scientific Inc.)

[0225] Chromatographic column: L column 2ODS5μm 2.1×150mm (Chemical Evaluation Research Institute)

[0226] Column temperature: 40°C

[0227] Mobile phase: 20 mM ammonium acetate 25% acetonitrile buffer

[0228] Analysis time: 10 minutes

[0229] Detector: DAD (Diode Array Detector)

[0230] Detection wavelength: 230nm

[0231] Flow rate: 0.3mL / min (isocratic elution)

[0232] Injection volume: 10 μL

[0233] <Quantitative determination of aluminum>

[0234] The amount of aluminum contained in the treated regenerated collagen fibers was quantified by the following method and is indicated in the table as "Component (B) Al量 " (Regarding Comparative Examples 2 and 3, no measurement was performed).

[0235] Reagents

[0236] Sulfuric acid: For precision analysis, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0237] Hydrochloric acid: For metal analysis, manufactured by Kanto Chemical Co., Ltd.

[0238] Sodium carbonate: Special grade, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0239] Boric acid: Special grade, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0240] Aluminum standard solution: 1000 mg / L for atomic absorption analysis, manufactured by Kanto Chemical Co., Ltd.

[0241] Ultrapure water: Ultrapure water production equipment Milli Q water, made by Millipore

[0242] Sample pretreatment method

[0243] Accurately weigh 0.1g of the sample in a platinum crucible, heat until no white smoke comes out, add a few drops of sulfuric acid, heat again until no white smoke comes out, and perform a full ashing treatment in a 550℃ electric furnace. Then, add 1g of alkaline flux (sodium carbonate: boric acid = 1:0.4) and melt in a 950℃ electric furnace. Cover with a watch glass, add 5mL of ultrapure water and hydrochloric acid (6mol / L), heat and dissolve on a heating plate at 70-80℃, cool, and make up to 50mL with ultrapure water. The resulting liquid is used as the measurement solution.

[0244] Preparation of standard curve solution

[0245] Aluminum standard solution (1000 mg / L) was used to prepare calibration curve solutions of 0.1 to 20 mg / L. Alkaline flux and hydrochloric acid were added to each solution at the same level as the sample.

[0246] Determination

[0247] The prepared sample was subjected to the determination of each element by ICP emission spectrometry under the following conditions.

[0248] Analytical device: iCAP6500Duo (manufactured by Thermo Fisher Scientific Inc.) Wavelength: Al396.152 nm RF power: 1150 W Cooling gas flow rate: 12 L / min Nebulizer flow rate: 0.70 L / min Auxiliary gas: 0.5 L / min Pump flow rate: 50 rpm

[0249]

[0250] Furthermore, the hair bundles processed in the above embodiments can be fixed to the hair by hairpins, etc., so that they can be used directly as hair extensions and can fully perform on a person's head.

Claims

1. A modified regenerated collagen fiber, wherein: The regenerated collagen fibers contain 1.0 mass % or more of the following component (A) as benzoic acid, (A) Benzoic acid or its salt.

2. The modified regenerated collagen fiber according to claim 1, wherein The content of the component (A) is 1.0 to 50% by mass as benzoic acid.

3. The modified regenerated collagen fiber according to claim 1, wherein The content of the component (A) is 5.0 to 40% by mass as benzoic acid.

4. The modified regenerated collagen fiber according to any one of claims 1 to 3, wherein It also contains the following ingredient (B), (B) A polyvalent metal or a salt thereof or a complex thereof.

5. The modified regenerated collagen fiber according to claim 4, wherein Component (B) is aluminum or a salt thereof or a complex thereof.

6. A method for processing regenerated collagen fibers, wherein: comprising the following steps (i), Step (i): a step of immersing regenerated collagen fibers in a fiber treatment agent containing the following component (A), (A) Benzoic acid or its salt.

7. The method for processing regenerated collagen fibers according to claim 6, wherein: The regenerated collagen fiber contains the following component (B), (B) A polyvalent metal or a salt thereof or a complex thereof.

8. The method for processing regenerated collagen fibers according to claim 7, wherein: Component (B) is aluminum or a salt thereof or a complex thereof.

9. A method for producing modified regenerated collagen fibers, wherein: include: A step of treating the regenerated collagen fibers by the method for treating the regenerated collagen fibers according to any one of claims 6 to 8.

10. A method for manufacturing a headdress product, wherein: include: A step of treating the regenerated collagen fibers by the method for treating the regenerated collagen fibers according to any one of claims 6 to 8.

11. A headwear product, wherein: The modified regenerated collagen fiber according to any one of claims 1 to 5 is contained as a constituent.